The Slavic theme in the novels by Miloš Crnjanski (Colloquia Comparativa Litterarum, 2025)
Miloš Crnjanski, the Slavic Cultural Community and the Dialogue among Slavic Nations.Valentina Sedefceva. The Slavic theme in the novels by Miloš Crnjanski / Milos Tsernianski. Veliko Tarnovo, Universitetsko izdatelstvo „Sv. sv. Kiril i Metodiy“, 2017.